Satisfaction and waiting time of users from peruvian health care centers: a secondary analysis of ENSUSALUD 2014-2016 - Murillo, Juan Pablo (2019)
Introduction: Health systems require evaluations about the quality of the delivery of services in Peru. Objective: Estimate the levels of satisfaction and waiting time in users of public and private peruvian health services. Methods: Secondary analysis of questionnaire 1 of the National Survey of Satisfaction of Users in Health (ENSUSALUD) 2014, 2015 and 2016. The waiting time was defined as the minutes it took since the user arrived at the health facility until he entered the doctor’s office. Satisfaction was evaluated with the user’s perception. Results: Satisfaction levels were: 70,1% (95% CI: 69,7%-71,2%), 73,7% (95% CI: 72,5%-74,9%) and 73,9% (IC 95%: 72,6%-75,1%) for 2014, 2015 and 2016, respectively. The users affiliated to the Comprehensive Health Insurance (2014: 67,7%, and 2016: 67,6%) and Social Health Insurance (EsSalud) (2015: 67,2%) were those that presented lower percentages. The regions that showed an increase in satisfaction were Cajamarca (2016-2014: 26%), La Libertad (2016-2014: 26%). The median waiting time was 60 (q1-q3:30-120), 75 (q1-q3:30-150) and 75 (q1-q3: 35-140) minutes, for the years 2014, 2015 and 2016, respectively. The delay in the attention was the most frequent problem identified by the users. Conclusions: In 2014, 2015 and 2016, 70,1%, 73,7% and 73,9% of users peruvian health services were satisfied with the care. We should consider the heterogeneity by territories and financial entity. The median waiting time for care was 60 minutes.